2019
DOI: 10.1101/570663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary stability of collateral sensitivity to antibiotics in the model pathogenPseudomonas aeruginosa

Abstract: 24Evolution is at the core of the impending antibiotic crisis. Sustainable therapy must thus 25 account for the adaptive potential of pathogens. One option is to exploit evolutionary trade-26 offs, like collateral sensitivity, where evolved resistance to one antibiotic causes 27 hypersensitivity to another one. To date, the evolutionary stability and thus clinical utility of 28 this trade-off is unclear. We performed a critical experimental test on this key requirement, 29using evolution experiments with Pseud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Currently, the bacteria evolution in multidrug environment is one of the major causes of drug resistance, whereby drug resistance mediated mutations become resistant to multiple drugs and can no longer be destroyed using the current antibiotic drug combination treatment approaches as it is [11]. Moreover, even though a patient who have been treated with drug combination therapy, the antimicrobial resistance pathogens including M. tuberculosis increase time to time and evolved into many multidrug and extensively drug-resistant strains, and achieving the STOP/End-TB strategy at the global level by 2035/2050 remains questionable and challenging, it is important to understand what are and how the influencing factors in multi-drug environment change treatment efficacy [12], that needs for designing novel effective drug [13] suggested that the proper selection of antibiotic drug combination therapy at the right dose and for the right length of time for crucial treatment efficacy, and necessitates by understanding the potential mechanisms of the influencing factors such as epistatic pathogen-host-antibiotic interactions and the frequency of mutations with pleiotropic fitness effects is the current critical and serious tasks in order to treat the patients efficiently and to slowdown the emergency and evolution of multidrugresistance bacterial strains, when the combined inhibitory effect of two drugs are stronger for their ability to clear infections under multi-drug environment [2].…”
Section: Antibiotic Combination Therapymentioning
confidence: 99%
“…Currently, the bacteria evolution in multidrug environment is one of the major causes of drug resistance, whereby drug resistance mediated mutations become resistant to multiple drugs and can no longer be destroyed using the current antibiotic drug combination treatment approaches as it is [11]. Moreover, even though a patient who have been treated with drug combination therapy, the antimicrobial resistance pathogens including M. tuberculosis increase time to time and evolved into many multidrug and extensively drug-resistant strains, and achieving the STOP/End-TB strategy at the global level by 2035/2050 remains questionable and challenging, it is important to understand what are and how the influencing factors in multi-drug environment change treatment efficacy [12], that needs for designing novel effective drug [13] suggested that the proper selection of antibiotic drug combination therapy at the right dose and for the right length of time for crucial treatment efficacy, and necessitates by understanding the potential mechanisms of the influencing factors such as epistatic pathogen-host-antibiotic interactions and the frequency of mutations with pleiotropic fitness effects is the current critical and serious tasks in order to treat the patients efficiently and to slowdown the emergency and evolution of multidrugresistance bacterial strains, when the combined inhibitory effect of two drugs are stronger for their ability to clear infections under multi-drug environment [2].…”
Section: Antibiotic Combination Therapymentioning
confidence: 99%